Expanding the MYBPC1 phenotypic spectrum: a novel homozygous mutation causes arthrogryposis multiplex congenita. Issue 1 (20th January 2016) - Ekhilevitch, N.; Kurolap, A.; Oz‐Levi, D.; Mory, A.; Hershkovitz, T.; Ast, G.; Mandel, H.; Baris, H.N.
Abstract : Arthrogryposis multiplex congenita (AMC) is characterized by heterogeneous nonprogressive multiple joint contractures appearing at birth. We present a consanguineous Israeli‐Druze family with several members presenting with AMC. A variable intra‐familial phenotype and pected autosomal recessive inheritance prompted molecular diagnosis by whole‐exome sequencing. Variant analysis focused on rare homozygous changes, revealed a missense variant in MYBPC1, NM_002465:c.556G>A (p.E286K), affecting the last nucleotide of Exon 8. This novel variant was not observed in the common variant databases and co‐segregated as expected within the extended family. MYBPC1 encodes a slow skeletal muscle isoform, essential for muscle contraction. Heterozygous mutations in this gene are associated with distal arthrogryposis types 1b and 2, whereas a homozygous nonsense mutation is implicated in one family with lethal congenital contractural syndrome 4. We present a novel milder MYBPC1 homozygous phenotype.